Differential security evaluation of Piccolo-like structure - Nianping WANG; Qing YIN (Tongxin xuebao)
In order to diversify the design of block cipher, Piccolo-like structure was proposed with principles of design.Security evaluation for Piccolo-like structure against differential cryptanalysis was deeply studied.By studying the input-output propagation characteristics of differential characteristics, the lower bound on the number of active round functions for arbitrary round Piccolo-like structure was given.The results show that, under the condition that the round functions are all bijective, there are at least l active round functions for l-round Piccolo-like structure if l≥6, and there are at least l-1 active round functions for l-round Piccolo-like structure if l is 1,2,3,4,5.